Qualitative Investigation: Exploring the Challenges Faced by Indonesian SMEs in Accessing Financial Services in Sukabumi City - Anton Priyo Nugroho (West Science Interdisciplinary Studies, 2023)
Indonesian SMEs play a crucial role in the country's economy, accounting for 99% of all businesses and employing more than 97% of the workforce. However, SMEs often face challenges in accessing financial services, hindering their growth and development. This study explored the challenges Indonesian SMEs face in accessing financial services in Sukabumi City, West Java. A qualitative research approach was employed, and data was collected through interviews and focus group discussions with 20 SME owners. The study's results identified several challenges and barriers SMEs face, including limited financial literacy and knowledge, limited access to formal financial services, high cost of financial services, and limited availability of appropriate financial products. To address these challenges, the study proposed several potential solutions, including financial education and literacy programs, reduced collateral requirements, the introduction of alternative financial services, improved availability of financial products, and government support. These solutions could help Indonesian SMEs in Sukabumi City access the financial assistance they need to grow and expand their businesses, contributing to the overall development of the country's economy.